Take me apart - Sligar, Sara, 1989- (MCD / Farrar, Straus and Giroux, 2020)
"A riveting debut novel of psychological suspense about a young archivist whose obsession with her subject's mysterious death threatens to destroy her fragile grasp on sanity"--